Desenvolvimento Urbano Sustentável e Planejamento Ambiental: impactos da expansão urbana e provisão habitacional na recente crise hídrica que atinge a RM de Goiânia - Elcileni de Melo Borges; Débora Ferreira da Cunha; Eduarda Marques da Costa; Celene Cunha Antunes Monteiro Barreira (Confins)
This paper presents an analysis on the environmental sustainability issue and the urban development policies implemented in Goiânia, from the first territorial planning experience developed with the transfer of the capital of Goiás (1930s) to the present, aiming to reflect on the scope and effectiveness of guidelines established, the adoption of environmental planning instruments, and the challenges to efficient urban management. Therefore, part of a brief review of the theoretical debate about the different interpretations of the concept "nature" and its interactions with man. Discusses the impacts of the intensification of the environmental crisis from the second half of the twentieth century, the application of the systemic approach in geography and the new tools for the treatment of the problems caused, as well as the emergence of environmental planning. Records the recurrence of "tensions" and antagonistic interests behind the concept of sustainable development and its evolution in the negotiations and agreements established in the main international forums, gaining greater emphasis on the New Urban Agenda (UN-HABITAT III) and the target of the Sustainable Development Objectives (until 2030). Finally, analyzes the overall picture of Brazilian urbanization, focusing on the specific case of the metropolitan area of ​​Goiânia, which records accelerated urban sprawl, scant control over land use and occupation and strong performance of real estate developers in the production of urban built environment, impacting on the degradation of its two main water supply sources (Meia Ponte and João Leite River) and the recent crisis of scarcity water that affects its population.